El proyecto de cuotas raciales y la afirmación del negro en Brasil - Rebecca Igreja (Centre de Recherches sur les Mondes Américains, 2009)
The debate about establishing racial quotas for the selection of candidates to universities is still polarized. In the academic world, there are positions in favor and against the idea. On one hand, there are statistics that evaluate the social differences between whites and blacks, trying to measure racism impact on the society. This data is considered as the irrefutable proof of racism evidence in Brazil and is used as the fundamental argument for those who advocate for racial quotas. On the other hand, there is the qualitative data trying to show the existence of areas historically shared by blacks and whites, and pointing out the social factor as a determinant for their different social positions. This data is used mainly by those who are against racial quotas, warning for the risks of “racializing” the Brazilian society, structured on a non-racialist thinking. Both positions, sometimes radical, led to a simplification of the Brazilian racial question, compromising not only the analysis about the current policies, but also its actual possibilities. In this article, I would like to discuss affirmative action in Brazil, focusing specially on the quota issue inside federal public administration.